I-O Psychology and Technology: Why Reinvent the Wheel?. Issue 4 (22nd November 2017) - Howard, Matt C.; Travers, Steven D.; Marshall, Chad J.; Cogswell, Joshua E.
Abstract : Morelli, Potosky, Arthur, and Tippins (2017 ) make a timely and appropriate call for authors to create conceptual models of technology in industrial-organizational (I-O) psychology. We agree with their call, but we believe that Morelli et al. overlooked the contributions of related fields that conduct research on technology in the workplace that are already consistent with their call. For this reason, we briefly detail other fields that commonly study the dynamics of technology and its influence on the workplace, followed by a discussion regarding the place of I-O psychology in the broader scheme of technology research. This discussion can aid future authors in conceptualizing appropriate contributions to the study of technology in I-O psychology as well as identifying whether these contributions benefit other fields. Perhaps more importantly, this discussion can help identify where I-O psychology fits in the broader scheme of technology research and which associated fields may be most readily available to aid in the creation of new models—two questions that currently seem unanswered.